A NOTE ON LACUNARY STATISTICALLY CONVERGENT DOUBLE SEQUENCES OF FUZZY NUMBERS - Altin, Yavuz (Korean Mathematical Soc, 2008)
In this paper we introduce and study lacunary statistical convergence for double sequences of fuzzy numbers and we shall also present some inclusion theorems.
Keywords: fuzzy number; statistical convergence